A study of histopathological spectrum of central nervous system lesions at a tertiary health care center of South Gujarat, India - Shihora, Nidhi V.; Patel, Himanshu U.; Patel, S. M.; Ramani, Pankaj R.; Nandasana, Bhumika N. (International Journal of Research in Medical Sciences, 2020)
Background: Central nervous system lesions can have varied aetiology like infectious, inflammatory and neoplastic. Establishing an accurate aetiology is essential for timely diagnosis and neurosurgical intervention. The annual incidence of tumours of CNS ranges from 10 to 17 per 100,000 people for intracranial tumours and 1 to 2 per 100,000 people for intraspinal tumours; the majority of these are primary tumours, and only one fourth to one half are metastastic. The present study attempts to provide preliminary data on morphological patterns of intracranial lesions and to study clinicopathological spectrum. Methods: The present study was carried out at a tertiary care center from January 2015 to September 2017. A total of 65 cases of CNS lesions were analyzed. In case of CNS tumours reporting were done according to WHO criteria for classification and grading. Results: Out of 65 cases studied, 51 cases (78.46%) were of neoplastic lesions and 14 cases (21.54%) of non-neoplastic lesions. Among 14 cases of non-neoplastic lesions 2 cases were of reactive/cystic lesions, 4 cases were of infective lesions, and 8 cases were of congenital lesions. In the present study, out of 51 neoplastic cases most common cases were of astrocytoma. Conclusions: The exact histopathological diagnosis of Central Nervous system lesions is essential to predict the prognosis and treatment. Management strategies and prognosis of tumours depends on the correlation of factors like the types, grades of tumours, its location, size and stage of development.